2021
DOI: 10.48550/arxiv.2101.04934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An $O(N)$ $Ab~initio$ Calculation Scheme for Large-Scale Moiré Structures

Tan Zhang,
Nicolas Regnault,
B. Andrei Bernevig
et al.

Abstract: We present a two-step method and the implemented code specifically tailored for band structure calculation of the small-angle moiré-pattern materials. These materials contain tens of thousands of atoms in a unit cell and the existing ab initio codes usually fail to do this within a finite amount of time without simplifying approximations. Our method can dramatically reduce the computational cost. Firstly, the self-consistent field calculation for ground state is performed with O(N ) Krylov subspace method impl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Intuitively, we assume there is a tight binding picture and the lattice is a rigid structure. Although previous formulations have suggested that lattice relaxation helps to isolate the flat band from other higher bands [22,26,44,45], for simplicity we do not consider lattice relaxation here. Note, since lattice relaxation can significantly modulate electron-phonon interaction and introduce strain in TBG, there may be nonvanishing torsion under our geometric theory.…”
Section: The Vierbein Formalism For Tbg and The Deformation Fieldmentioning
confidence: 99%
“…Intuitively, we assume there is a tight binding picture and the lattice is a rigid structure. Although previous formulations have suggested that lattice relaxation helps to isolate the flat band from other higher bands [22,26,44,45], for simplicity we do not consider lattice relaxation here. Note, since lattice relaxation can significantly modulate electron-phonon interaction and introduce strain in TBG, there may be nonvanishing torsion under our geometric theory.…”
Section: The Vierbein Formalism For Tbg and The Deformation Fieldmentioning
confidence: 99%